Global Challenges in the Provision of Theranostic Services the International Atomic Energy Agency (IAEA) Perspective - Brink, Anita; Cerci, Juliano J.; Giammarile, Francesco; Yurystovskyi, Danylo; Korde, Aruna; Estrada-Lobato, Enrique; Mikhail-Lette, Miriam; Pellet, Olivier; Macapinlac, Homer A.; Paez, Diana (World Journal of Nuclear Medicine, 2025)
The global expansion of theranostics, a field combining molecular imaging and targeted therapy, has accelerated with the Food and Drug Administration approvals of Lutathera and Pluvicto. However, significant challenges hinder equitable access, particularly in low- and middle-income countries (LMICs). These include infrastructure limitations, such as the high cost of gamma cameras, positron emission tomography/computed tomography scanners, cyclotrons, and maintenance, as well as disparities in the availability of radiopharmaceuticals. In LMICs, one single-photon emission computerized tomography scanner may serve 33 million people, compared with 57,000 in high-income countries. Furthermore, shortages of key isotopes like 99Mo and 177Lu highlight vulnerabilities in global supply chains.Staffing and training are critical issues, as delivering theranostic services requires specialized teams that are often scarce in LMICs. The International Atomic Energy Agency (IAEA) addresses these challenges by offering training programs, developing databases like IMAGINE and NUMDAB, and fostering technical cooperation among member states. To improve access to theranostic services, strategies such as using alternative imaging methods and enhancing local radiopharmaceutical production are recommended.The IAEA's Rays of Hope initiative aims to strengthen regional capacities, improve infrastructure, and address the critical shortage of trained professionals. A coordinated global effort is essential to overcome these barriers, reduce costs, and ensure equitable access to theranostics, particularly in resource-limited settings.
Keywords: global challenges; IMAGINE database; International Atomic Energy Agency; NUMDAB database; theranostics